1978
DOI: 10.1007/bf00221599
|View full text |Cite
|
Sign up to set email alerts
|

The epidermis and sensory organs of Dugesia tigrina (Turbellaria: Tricladida)

Abstract: The epidermis of D. tigrina was examined using the scanning electron microscope. Both dorsal and ventral surfaces are extremely irregular in contour, as well as being permeated by large numbers of pores. Cilia are restricted to the ventral surface, the auricles and that part of the dorsum adjacent to the auricles. Club-shaped receptors, as well as cilia, were seen in the auricles. The epidermis anteriad to the eyespots is indistinguishable from that covering the remainder of the dorsal surface. Light rays coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
2

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 6 publications
1
16
1
2
Order By: Relevance
“…3). This finding differs from that observed with Dugesia tigrina from Smales and Blankespoor (1978), who described it as irregularly contoured. Another different point was the presence of a remarkable invagination on the epidermis of the anterior region and below the auricles in Girardia sp.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…3). This finding differs from that observed with Dugesia tigrina from Smales and Blankespoor (1978), who described it as irregularly contoured. Another different point was the presence of a remarkable invagination on the epidermis of the anterior region and below the auricles in Girardia sp.…”
Section: Discussioncontrasting
confidence: 99%
“…4A,C). Ciliated structures were not abundantly visualized in this study since they are structures commonly found in the ventral surface of Girardia tigrina and on the dorsal surface, especially in areas such as the auricles, although they can also be observed in the dorsal epidermis of other species (Smales and Blankespoor, 1978). …”
Section: Discussionmentioning
confidence: 78%
“…Further studies will elucidate whether, in a WT situation, both paralogs are involved in signal transduction for a single Wnt ligand. (25,26). To address whether Smed-dvl-1/2 functions as a component of the PCP network, we analyzed the polarization of the ventral epithelium after Smed-dvl-1/2 interference.…”
Section: Resultsmentioning
confidence: 99%
“…Because the positioning of the basal bodies is governed by actin assembly, we analyzed the role of Smed-dvl-1/2 in the assembly of the actin network and in the docking of the basal bodies in the planarian epithelium. The actin filaments are arranged as a network that defines each cell border and contains regular openings to allow mucus secretion by the rhabdomeres (25). Silencing of Smed-dvl-2 dramatically affected the arrangement of this network, resulting in an irregular net in which the cell borders and rhabdomere openings were not visible (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Only recently has scanning electron microscopy been applied increasingly to the Turbellaria (e.g. Reuter 1978;Smales & Blankespoor 1978;Williams 1978). The order Tricladida figured greatly in the early phase of Turbellarian fine structural research (e.g., Klima 1959Klima , 1961Pedersen 1959aPedersen , b, 1961aSkaer 1961) but the interest soon expanded to include other orders, especially the Acoela (e.g.…”
Section: Introductionmentioning
confidence: 99%